An Analysis of 34, 218 Pediatric Outpatient Controlled Substance Prescriptions. Issue 4 (August 2016) - George, Jessica A.; Park, Paul S.; Hunsberger, Joanne; Shay, Joanne E.; Lehmann, Christoph U.; White, Elizabeth D.; Lee, Benjamin H.; Yaster, Myron
Abstract : (Abstracted from Anesth Analg, 122:807–813, 2016) Medication errors can cause serious and often preventable injuries. Studies have found that most errors occur at the stage of prescription writing or drug ordering.